Patenty uprawniające do uprawiania turystyki wodnej na jachtach żaglowych – zagadnienia prawne - Jakubowski, Aleksander (Studia Prawa Publicznego, 2019)
The article considers the issue of sailing licences which include: a sailor licence, a steersman licence and a captain licence. The legal character of sailing licences and the procedure in which they are issued is analysed. The judicial control of sailing licences is also considered. The granting of a sailing licence is an act confi rming that a person indicated therein has certain qualifi cations required for sailing. The legal character of the licence is similar to an administrative certifi cate. Granting the sailing licence can be conditional upon passing a formal examination by a person requesting the licence to be issued. The examination itself is regarded as an administrative act in law. The study proves that the Polish Sailing Association performs a function of a public administration unit issuing sailing licences. This means that it acts as a an administrative body in a functional dimension.The sailing licence is granted in the form of a declarative decision issued by the Polish Sailing Association. The proceeding for issuing such a decision is an administrative proceedings governed by the Code of Administrative Proceedings. The actions of the Polish Sailing Association as well as its failure to act are controlled by administrative courts.